The influence of fatty acids in vitro on mammalian cells from species differing in their fatty acyl desaturase capabilities - Fubbs, Joanmariae Louise; Giangregorio, Giangregorio (My University, 1991)
Numerous studies have assessed the effects of single fatty acids on various aspects of lipid metabolism, particularly cancer. Established cell lines have largely been used for this purpose. The choice of control cells. however, has often been inappropriate. There is also a surprising lack of knowledge of the effects of fatty acids in the "real world", in which normal cells in vivo are presented with mixtures of dietary fatty acids. Before transformed cells can be used as models of disease states, it is essential to fully understand fatty acid metabolism in normal (control) cells. Only then can experimental findings be extrapolated to the clinical situation with some certainty. This thesis has therefore, assessed the effects of exogenous fatty acid mixtures on the growth/viability of normal mammalian tissues all cultured under standard conditions, and attempted to elucidate the mechanisms underlying such effects. As different mammalian species exhibit different fatty acyl desaturase capabilities, cells from three species were chosen, viz. rat, Man and cat, with desaturase capability decreasing with species, respectively. A wide range of different cell types from each species were studied due to the known differences in their lipid profiles and metabolism. The cells studied in the rat and cat included those derived from the cerebral cortex. white adipose tissue, skin, lung, skeletal muscle and aortic endothelium, while the human cell obtainable included those derived from skin, types skeletal muscle and lung. Erythrocytes and lymphocytes were studied in all 3 species. 'Each of the cultured normal mammalian tissues studied were shown to exhibit different proliferation rates. Cultured cells were dosed with fatty acid mixtures mimicking the fatty acid composition of dietary oils; these mixtures were termed 'pesudo-oils", were bound to bovine serum albumin as carrier, dosed at concentrations ranging from 0 to 100mg/l, and cultures incubated for 48 hours. Viable cell numbers were assessed and related to control cell numbers at the time of dosing. This was termed the 'cytostatic number", and its implications were discussed. pseudo-Oils modulated cell viability, but the extent thereof varied considerably in magnitude with pseudo-oil and concentration dosed. Furthermore, differences in cell viability were shown both between tissues from a particular species, as ........ between identical cultured tissues derived from different species. In general, pseudo-oil supplementation of cultures induced an overall concentration dependant growth limiting and/or cytotoxic effect. Proliferation of certain cell types were, however, stimulated with some pseudo-oils, particularly at low to intermediate concontrations in the range dosed. Differences in cell viability were also related to the degree of pseudo-oii unsaturation; the two most saturated oils, meat and coconut, were in general, least effective in limiting and/or promoting cell viability, while the effects induced with pseuciooils rich in polyenoic fatty acids were more marked. The possibility that the cell viability changes induced were related to albumin as fatty acid carrier, or fetal calf serum as a supplement in the incubation medium, were investigated, and the possibility discounted. The use of pseudo-oils rather than single fatty acids, however~ warrants consideration of fatty acid synergism and antagonism. To establish the possible mechanism(s) whereby the dosed pseudo-oils inf!uenced cell viability, various cell parameters were subsequently examined. These included total protein, the incorporation, desaturation and elongation of both pseudo-oil, and single C18, fatty acids, as well as the production of lipoperoxides and prostanoids. total cellular protein concentrations varied both between tissues and species, and reflected changes in cell number in dosed cells However, pseudo-oils were also shown to modulate absolute protein synthesis in nucleated mammalian cells, primarily by enhancing such. It was postulated that this related to the induction of lipid merabolising enzymes. Variations in cellular fatty acid composition were found both between the mammalian tissues and species studied. Evidence to support the capability of cultured mammalian cells to incorporate exogenous fatty acids was shoun. The extent of incorporationr however, varied with cell type, species and fatty acid structure. Desaturase cascade enzyme capability was also assessed by comp~rison o~ dosed cell FA profiles witn that of controls. Once again, desatwration and elongation capability varied with different cell types within a particular species, independent of cell proliferation rates, but was generally greatest in dividing rat, lower in human, and least in cat, tissues. In all three species, however, erythrocytes and lymphocytes failed to efficiently perform these reactions. This correlated with the lower threshold for Cytotoxicity in lymphocytes and erythroctyes than in dividing cells, although desaturation capability did not correlate directly with proliferation rates in growing cells. It was nevertheless clearly shown that desaturase cascade enzyme expression with pseudo-oil dosage was more limited than, and could not be fully predicted by, the results obtained utilising single FA's. This phenomenon was related, to synergism and antagonism between pseudo-oil FA's. Cultured mammalian tissues were found to vary in their capability to form both lipoperoxides and eicoeanoide , Pico-molar amounts of total eicoesanoide were quantitated compared to nano-molar lipid peroxide amounts of lipid peroxides. production was not directly related to control cell proliferation rates or total unsaturated FA levels. However, total molar eicosanoid concentrations in control cells and the eicosanoid:MDA ratio suggested a correlation with the desaturation capabilities of the three species, decreasing in the order rat exhibited > human > cat each cell type studied a unique prostanoid profile, which was modulated (enhanced~ suppressed or inhibited) to a greater or lesser extent with pseudo-oil incubation. However. no correlation between cell viability, the degree of pseudo-oil unsaturation, or any other biochemical parameter studied except pseudo-oil concentration dosed, could be proven to relate to the changes in prostanoid levels induced with pseudo-oil supplementation. This implied that endogenously biosynthesised prostanoida were not directly responsible for' effects induced. On the other hand, lipoperoxide production generally increased with pseudo-oil concentration dosed and was greater wi th pseudo oils rich in Polyenoic than moroenoic or saturlted FA's. Furthermore lipoperoxide involvement in the modulation mammalian cell proliferation was proposed, however, was shown not to be the sole mechanism, and the involvement of membrane structural changes, ego fluidity was The findings indicated that the modulation of cell proliferation by FA"s was multifactorial, The variations found between rat, cat and human tissues with regard to the parameters investigated indicated that extrapolation of experimental results between mammalian tissues and species, as well as the use of cells from different tissues and particularly from different species as controls for other cells, is potentially misleading, and should be avoided if reliable interpretation of results is desired. Further more, we recommend fatty acid analysis of all culture media prior to use, and appropriate supplementation with polyenoic, required. or at least essential, fatty acids if Since p-oil FA composition reflected that of dietary oiIs, the data from this thesis serves as an in vitro model and guide to how normal genetically entire mammalian cells in vivo may respond when similar oils form part of the dietary intake.
A Thesis submitted to the Faculty of Medicine, in fulfilment of the Requirements for the Degree of Doctor of Philosophy
Keywords: Fatty Acids.